Developing Students’ Reading Culture for Academic Reading Level through Metacognitive Strategies - Pranowo pranowo (Bina Nusantara University, 2018)
The development of reading culture for this academic level used the metacognitive strategies. This research was a case study in wihich the data sources were randomly drawn from various print sources by cutting off the core of the text to be analyzed. The technique of data analysis was done with two steps. The first step was to identify each data based on the categories that contained in the cognitive domain. The second step was the results of the analysis of the cognitive domains viewed based on the metacognitive strategies that included the process of planning, monitoring, and evaluate. The results of the research are that reading culture at the academic level can be developed through metacognition strategy. The steps that can be done are the reader performs cognitive process starting from remembering, understanding, applying, analyzing, evaluating, and creating. Then, every cognitive process is reviewed that the Academic reading culture can be developed with metacognitive strategies that are the type of intensive reading includes, reading comprehension, reading critically, reading creatively, reading interpretative, and reading reflective.